2019
DOI: 10.1002/app.48567
|View full text |Cite
|
Sign up to set email alerts
|

Breathable polymeric materials based on high‐density polyethylene prepared by environmental crazing

Abstract: This work addresses the preparation of breathable materials based on high‐density polyethylene (HDPE) and characterization of their performance. The sustainable HDPE mesoporous materials were prepared by the tensile drawing of the HDPE films in the presence of physically active liquids (PALEs) via the mechanism of environmental intercrystallite crazing (EIC). The prepared mesoporous materials were characterized by the different physicochemical methods such as differential scanning calorimetry (DSC), atomic for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…[ 23–26 ] At present, it has been revealed that crazed polymers are permeable for gases, water vapor, and liquids. [ 27,28 ] Moreover, the formed porous structure enables one to use crazed polymers as matrices for incorporating low‐ and high‐molecular weight compounds, that is, for the preparation of nanocomposites (NCs). [ 29–31 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 23–26 ] At present, it has been revealed that crazed polymers are permeable for gases, water vapor, and liquids. [ 27,28 ] Moreover, the formed porous structure enables one to use crazed polymers as matrices for incorporating low‐ and high‐molecular weight compounds, that is, for the preparation of nanocomposites (NCs). [ 29–31 ]…”
Section: Introductionmentioning
confidence: 99%